Dampak Negative Illegal Logging Terhadap Indonesia - Boediningsih, Widyawati; Tandiono, Sidharta (Faculty of Law, University of Dr. Soetomo, 2022)
The method used in this paper is the normative method which contains Illegal logging which is the main problem in Indonesian forestry mining. The impact of illegal logging in addition to economic losses due to the shortage of wood in Indonesia, there is also a major problem, namely the unique flora and fauna in Indonesia are threatened, therefore Indonesia provides strict rules or sanctions for those who carry out this crime. is the weakness of the government in overcoming illegal logging actions. In this case the government should be aware and provide strict safeguards in Indonesian forest areas Key words: illegal logging, forestry and sanctions